2005
DOI: 10.1080/009140390504762
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure Characterization of Boron-Nitrogen Containing Phenol Formaldehyde Resin

Abstract: A boron-nitrogen modified phenol formaldehyde resin (BNPFR) was prepared from phenol, formalin, ammonia water, n-butyl alcohol, boric acid, and paraformaldehyde. The reaction mechanism and structure of BNPFR during the synthesis and curing process were investigated by FTIR, NMR. The thermal stability was determined by thermogravimetric analysis. The results showed that borate, ether linkage, methylene bridges, and hexatomic ring containing coordinate linkage of boron-nitrogen were formed mostly in the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…However, the aforementioned modified 5 wt% SWCNTs PF resol resin peaks became weaker, which indicated that excess additions of SWCNTs could seriously affect the basic molecular structure of the modified PF resol resin. These results were consistent with previous FT-IR studies of PF resins (Gao et al 2005;Poljansek and Krajnc 2005;Chen et al 2008;Alshawi et al 2019).…”
Section: Fig 2 Ft-ir Spectra Of the Resinssupporting
confidence: 93%
“…However, the aforementioned modified 5 wt% SWCNTs PF resol resin peaks became weaker, which indicated that excess additions of SWCNTs could seriously affect the basic molecular structure of the modified PF resol resin. These results were consistent with previous FT-IR studies of PF resins (Gao et al 2005;Poljansek and Krajnc 2005;Chen et al 2008;Alshawi et al 2019).…”
Section: Fig 2 Ft-ir Spectra Of the Resinssupporting
confidence: 93%
“…Compared with the unmodied phenolic resin (curve a), a new absorption band at 1361 cm À1 corresponding to the B-O bond appears (curve b). 27 It means that the boron element is introduced into the backbone of the phenolic resin.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band at 1396 cm À1 corresponds to B-O bond. 27 Aer carbonization, the bands at 1100 cm À1 (CH 2 OH), 1450 cm À1 (-CH 2 -) and 2900 cm À1 (-CH 2 ) almost disappear, indicating resole decomposition and small molecular volatilization. However, the B-O absorption band is still observed in B-OMCs, suggesting that boron has been introduced into the backbone of the phenolic resin and well preserved aer calcination at 600 C. The precise formation of B-OMCs was further analyzed by Xray photoelectron spectroscopy (XPS), and the results are shown in Fig.…”
Section: Chemical State Of B-omcsmentioning
confidence: 99%
“…31 Total oxygen group of B-OMCs reaches 10.40 wt%, much higher than that of undoped OMCs (4.3 wt%). 27 The enriched oxygen groups on the carbon surface will be benecial to the capacitance retention at a high scan rate. 32…”
Section: Chemical State Of B-omcsmentioning
confidence: 99%